Review of Leishmaniasis in the Middle East and North Africa - Tabbabi, Ahmed (African health sciences, 2019)
Background: Cutaneous and visceral forms of leishmaniasis are the most important protozoan infection in the Middle East and North Africa (MENA). Objectives: Review the current knowledge on leishmaniasis in the MENA. Methods: The data presented in this review are gathered primarily from WHO reports and from an extensive literature search on PubMed. Results: There are four cycles of transmission of leishmaniasis: zoonotic cutaneous leishmaniasis (ZCL), induce by Leishmania (L.) major, transmitted by Phlebotomus ( P.) papatasi , with rodent species of Psammomys obesus , Meriones libycus , Nesokia indica , and Rhombomys opimus are considered as host reservoirs. Zoonotic visceral leishmaniasis (ZVL) is inducing by L. infantum, transmitted by several Phlebotomus spp. of the sub-genus Larroussius and mainly P. perniciosus in more than one-half of the MENA countries and the dog species of Canis familiaris are considered as the main reservoirs. Anthroponotic cutaneous leishmaniasis (ACL), induce by L. tropica and transmitted by P. sergenti , without any non-human reservoir in most cases. Anthroponotic visceral leishmaniasis (AVL) induces by L. donovani spreads through P. alexandri , circulates exclusively in humans. Conclusion: There are many challenges facing the successful control of leishmaniasis. However, there is continuing research into the treatment of leishmaniasis and potentially vaccinations for the disease. DOI: https://dx.doi.org/10.4314/ahs.v19i1.4 Cite as: Tabbabi A. Review of Leishmaniasis in the Middle East and North Africa. Afri Health Sci. 2019;19(1): 1329-1337. https://dx.doi. org/10.4314/ahs.v19i1.4